Nickel-Catalyzed Reductive Cross-Coupling of Imines with α-Imino Esters for the Construction of α,β-Diamino Acid Derivatives - Zhang, Jian; Tao, Zhonglin (Synthesis, 2025)
A nickel-catalyzed reductive cross-coupling reaction of different imines has been developed. This method enables the first reductive cross-coupling between aryl/alkyl imines and α-imino esters, affording α,β-diamino acid derivatives bearing quaternary carbon centers in a single-step process. This imine umpolung strategy exhibits several advantages, such as mild conditions and broad functional group compatibility.
Keywords: Nickel catalysis; Imines; α-Imino esters; Reductive cross-coupling; α,β-Diamino acid derivatives